2020
DOI: 10.1177/0269215520933950
|View full text |Cite
|
Sign up to set email alerts
|

Prehabilitation in patients awaiting elective coronary artery bypass graft surgery – effects on functional capacity and quality of life: a randomized controlled trial

Abstract: Objective: To determine the impact of an exercise-based prehabilitation (EBPrehab) program on pre- and postoperative exercise capacity, functional capacity (FC) and quality of life (QoL) in patients awaiting elective coronary artery bypass graft surgery (CABG). Design: A two-group randomized controlled trail. Setting: Ambulatory prehabilitation. Subjects: Overall 230 preoperative elective CABG-surgery patients were randomly assigned to an intervention (IG, n = 88; n = 27 withdrew after randomization) or contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 43 publications
1
69
0
10
Order By: Relevance
“…Dos quatro artigos selecionados, um tratava-se de uma pesquisa de intervenção sem grupo controle (GIMENO-SANTOS et al, 2019), e três eram Ensaios Clínicos com grupo controle (SAWATZKY et al, 2014;STEINMETZ et al, 2020;MOSTAFA et al, 2020).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Dos quatro artigos selecionados, um tratava-se de uma pesquisa de intervenção sem grupo controle (GIMENO-SANTOS et al, 2019), e três eram Ensaios Clínicos com grupo controle (SAWATZKY et al, 2014;STEINMETZ et al, 2020;MOSTAFA et al, 2020).…”
Section: Resultsunclassified
“…Ainda sim, um estudo incluiu pacientes em espera de transplante cardíaco (GIMENO-SANTOS et al, 2019), e os demais elegeram indivíduos no pré-operatório de revascularização do miocárdio (SAWATZKY et al, 2014;STEINMETZ et al, 2020) e/ou substituição valvar (MOSTAFA et al, 2020). No que se refere aos objetivos, dois estudos avaliaram a viabilidade da PR (SAWATZKY et al, 2014;GIMENO-SANTOS et al, 2019), enquanto outros dois investigaram seus efeitos (STEINMETZ et al, 2020;MOSTAFA et al, 2020). Fonte: Dados da pesquisa (2020).…”
Section: Resultsunclassified
“…These results suggest that aortic surgery, compared with other cardiac surgeries, is more likely to interfere with post-operative recovery. As an approach to early recovery of physical functions, it has been reported that interventions such as pre-operative rehabilitation and pre-operative education are effective in improving post-operative physical and mental functions in CABG and valve surgery [34][35][36]. However, because aortic surgery often involves emergency surgery associated with aneurysm rupture or dissection and because there is a risk of rupture even in cases that are asymptomatic and discovered incidentally [37], it is often impossible to take measures such as rehabilitation intervention pre-operatively.…”
Section: Discussionmentioning
confidence: 99%
“…Portanto, essa estratégia facilitou a estruturação desta pesquisa e a formulação do seguinte questionamento: "Quais são as evidências científicas existentes sobre a efetividade da PR nos desfechos pré e pós-operatórios de pacientes submetidos à cirurgia cardíaca?". A fim de se encontrar respostas, foi realizada uma revisão integrativa da literatura, em julho de 2020, a partir da leitura de artigos identificados nas bases de dados Dos quatro artigos selecionados, um tratava-se de uma pesquisa de intervenção sem grupo controle (GIMENO-SANTOS et al, 2019), e três eram Ensaios Clínicos com grupo controle (SAWATZKY et al, 2014;STEINMETZ et al, 2020;MOSTAFA et al, 2020).…”
Section: Metodologiaunclassified
“…Com relação ao ano de publicação, variou entre 2014 e 2020. Ainda sim, um estudo incluiu pacientes em espera de transplante cardíaco (GIMENO-SANTOS et al, 2019), e os demais elegeram indivíduos no pré-operatório de revascularização do miocárdio (SAWATZKY et al, 2014;STEINMETZ et al, 2020) e/ou substituição valvar (MOSTAFA et al, 2020). No que se refere aos objetivos, dois estudos avaliaram a viabilidade da PR (SAWATZKY et al, 2014;GIMENO-SANTOS et al, 2019), enquanto outros dois investigaram seus efeitos (STEINMETZ et al, 2020;MOSTAFA et al, 2020).…”
Section: Metodologiaunclassified